Microstructural Underpinnings of Giant Intrinsic Exchange Bias in Epitaxial NiCo2O4 Thin Films - Detian Yang; Arjun Subedi; Chao Liu; Haile Ambaye; Valeria Lauter; Peter A. Dowben; Yaohua Liu; Xiaoshan Xu (Advanced Electronic Materials)
Abstract Understanding intrinsic exchange bias in nominally single‐component ferromagnetic or ferrimagnetic materials is crucial for simplifying related device architectures. However, the mechanisms behind this phenomenon and its tunability remain elusive, which hinders the efforts to achieve unidirectional magnetization for widespread applications. Inspired by the high tunability of ferrimagnetic inverse spinel NiCo2O4, the origin of intrinsic exchange bias in NiCo2O4 (111) films deposited on Al2O3 (0001) substrates are investigated. The comprehensive characterizations, including electron diffraction, X‐ray reflectometry and spectroscopy, and polarized neutron reflectometry, reveal that intrinsic exchange bias in NiCo2O4 (111)/Al2O3 (0001) arises from a reconstructed antiferromagnetic rock‐salt NixCo1‐xO layer at the interface between the film and the substrate due to a significant structural mismatch. Remarkably, by engineering the interfacial structure under optimal growth conditions, it can achieve exchange bias larger than coercivity, leading to unidirectional magnetization. Such giant intrinsic exchange bias can be utilized for realistic device applications. This work establishes a new material platform based on NiCo2O4, an emergent spintronics material, to study tunable interfacial magnetic and spintronic properties.